O(s) cronotopo(s) de As visitas do dr. Valdez de João Paulo Borges Coelho: uma análise sob a perspectiva dialógica - Lemes, Cinthia Aparecida (2023)
In this study, the analysis of the chronotope in the novel As visitas do Dr. Valdez by João Paulo Borges Coelho is approached from Bakhtin's theoretical perspective. The corpus involves a fictional narrative that explores a series of historical events that occurred in Mozambique, from the forced decolonization in the early 1960s to the roots of the country's formation. The author's aim is to provide answers to open questions within the larger historical context, with the intent of circumventing the imagery constructed during the colonial period. It is at this point that spaces and times blur, and the writer creates characters who give voice to those that were not recognized during the colonial era, such as women and servants. In addition to addressing forced decolonization, the discourses also delve into the ideological markers of Mozambique's history, reflecting the socio-cultural stances generated during and before colonization. This study is guided by the hypothesis that the interaction between the different voices employed will generate a debate that will wear down certain ideological positions, revealing the perspectives of both colonizers and the colonized, as well as the tension existing between these relationships. As a result, a deeper understanding of Mozambican culture, including its perspectives and hierarchical structures, is the ultimate goal. This makes Bakhtin's and the Circle's theories highly relevant. Metaphorical resources and theatricalization expose an intricate and emblematic society, offering an opportunity for a reevaluation of history, memory, and anthropological relationships in Mozambique.The disruption of this pattern of thought, which we refer to in our research as the "living room chronotope," not only influenced how the conversation participants thought but also has the potential to impact the thinking of readers willing to reconsider the history of Mozambique